Pelaksanaan Konseling Kesehatan Pra Nikah Terhadap Persiapan Kehamilan Yang Sehat Pada Remaja Di Desa Namorih Kecamatan Pancurbatu Tahun 2024 - Ninsah Mandala Putri Br. Sembiring; Emma dosriamaya Simanjuntak; Desy Ratna sari Sembiring (BADAN PENERBIT STIEPARI PRESS, 2024)
Premarital health counseling is an important effort to prepare teenagers for marriage and family life, including planning a healthy pregnancy. This research aims to explore the implementation of pre-marital health counseling to prepare for a healthy pregnancy among teenagers in Namorih Village, Pancurbatu District, in 2021. The research method used is a qualitative study with a descriptive approach. Data was collected through in-depth interviews with health counselors and teenagers who had attended premarital counseling. The research results show that pre-marital health counseling in Namorih Village is carried out in a structured manner with a focus on understanding reproductive health, the importance of careful pregnancy planning, and efforts to prevent maternal and child health risks. However, there are still challenges related to limited access to information and active participation of adolescents in counseling. It is hoped that the results of this research can provide input for the development of premarital health counseling programs that are more effective and relevant for teenagers in various regions.